The Effect of Peer Group Support on Motivation to Quit Smoking Among Adolescents - Ilma Widiya Sari (Universitas Nahdlatul Ulama Surabaya, 2022)
Adolescents use cigarettes without considering the consequences and lack awareness about the dangers of using cigarettes. Peer group support potentially motivates to quit smoking in adolescents. It can empower group members by providing a role model to increase motivation. This paper analyzes the effect of peer group support on motivation to quit smoking among adolescents. It was quasi-experimental research with a post-test and pre-test one-group design. The population was smoking adolescents. In addition, there were 37 respondents with purposive sampling. The inclusion criteria were male teenagers aged 12-16 years and active smokers. The independent variable was peer group support, and the dependent variable was motivation to quit smoking. The instrument to assess motivation to quit smoking was the Richmond Test. Data analysis utilized paired t-test with α=0.05. There was an increase in the mean value of motivation to quit smoking before and after the intervention. In addition, paired t-tests obtained p=0.030 (p< 0.05), indicating a significant difference in pre-test and post-test. Thus, there was an effect of peer group support on adolescents' motivation to quit smoking. In conclusion, peer group support can increase adolescents' motivation to quit smoking. Nurses could enhance motivation for smoking cessation through peer support interventions so there is a change in smoking behavior in adolescents. Further study should use a control group and a larger sample size.